PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN JIGSAW TERHADAP PRESTASI BELAJAR BIOLOGI DITINJAU DARI MOTIVASI BERPRESTASI SISWA - Devi Setiawati; Bambang Sahono (UNIB Press, 2022)
This research aims to describe the effect of the Group Investigation (GI) and Jigsaw cooperative learning model on learning achievement in Biology in terms of student achievement motivation. The design used in this study was the experimental squasi with 2 x 2 factorial design. Data collection was carried out by observation and tests, the subject of experimental research was students of class X MIPA. The sample selection is done by using purposive random sampling technique. The experimental class is X MIPA 1 and the control class is X MIPA 3. From the results of the study it was concluded that students who studied with the cooperative learning model of the Group Investigation (GI) type had higher learning achievement than students who studied with the Jigsaw type, students who had high achievement motivation had higher learning achievement than students who had low achievement motivation, and there was interaction between student achievement motivation and learning achievement Biology at State High School 1 Lahat.